Barbarian Digital Society: A Legal Philosophy Perspective on Efforts to Overcome the Moral Degradation of Indonesian Netizens - Ferry Irawan Febriansyah; Aldo Redho Syam; Vivi Ayudya Permatasari (Universitas Negeri Surabaya, 2024)
The